Facilitating Expert Consensus on Stormwater Pond Management - Cody Gusto; Paul Monaghan; Basil V. Iannone III (The Journal of Public Interest Communications, 2026)
Stormwater ponds are common engineered features in residential landscapes designed to control flooding and capture polluted, nutrient-rich runoff, yet they frequently underperform intended ecosystem service functions. Growing evidence suggests that pond management, governance, and communication factors in residential communities are influential. This study used a three-round Delphi process with 34 Florida stormwater pond experts to identify consensus-based barriers, success strategies, and future trends shaping effective pond management. Panelists reached consensus on 13 barriers, 26 strategies, and four trends, prioritizing entrenched lawncare norms, reactive budgeting, limited environmental knowledge, weak contractor oversight, and increasing storm and nutrient-loading pressures. Findings suggest improving outcomes requires communication that clarifies responsibility, normalizes visible best management practices, supports proactive budgeting, and embeds ecological priorities within HOA governance.